Предмет: Математика,
автор: anonymous5611
a +(96 - (53 + b)) + (79 - c) если а = 14, b = 13, с = 17. СРОЧНО
Ответы
Автор ответа:
1
Ответ:
Ответ : 106
Пошаговое объяснение:
подставляем в решение цифры:
14+(96-(53+13))+(79-17) = 14+ (96- 66) + 62 = 14+ 30 + 62 = 44 + 62 = 106
(Раскрываем скобки)
Автор ответа:
1
Ответ:
а+(96-(53+b))+(76-c)=14+(96-(53+13))+(79-17)=14+30+62=34+62=106
Похожие вопросы
Предмет: Математика,
автор: ZakaMakaFaka
Предмет: Английский язык,
автор: КрАсОтКаСБаШнИ
Предмет: Русский язык,
автор: 12357788
Предмет: Литература,
автор: sashaKim221
Предмет: Английский язык,
автор: 55Umnik55